Evidence for an H2 promoting effect in the selective catalytic reduction of NOx by propene on Au/Al2O3. Issue 4 (26th November 2014) - Chaieb, Tesnim; Delannoy, Laurent; Casale, Sandra; Louis, Catherine; Thomas, Cyril
Abstract : This work provides the first experimental evidence of the H2 effect in C3 H6 -SCR over a Au/Al2 O3 catalyst. The key point is a fine control of the number of surface Au sites. Abstract : This work provides the first experimental evidence of an H2 effect in C3 H6 -SCR over an Au/Al2 O3 catalyst. This effect could only be observed when the number of Au catalytic sites was decreased. The N2 turnover rate estimated for the first time for the Au catalytic sites for H2 –C3 H6 -SCR was found to be similar to that estimated for Ag ones supported on Al2 O3 .